Performance test of greenhouse effect (GHE) vent dryer with the addition of paraffin as a heat storage medium. Issue 1 (November 2021) - Mustaqimah,; Ahmar, A; Nurba, D
Abstract: Green House Effect (GHE) vent dryer is a kind of dryer design by utilizing solar energy as a drying energy source. Adding paraffin as a heat storage medium is one solution so that the GHE vent dryer can operate when the solar energy has dimmed. The purpose of this study was to test the performance of heat storage media using paraffin as a heat storage medium. 9 kg of paraffin was prepared, put into 9 copper pipes and placed in the absorber chamber. The data measured were the temperature in the drying room (T1=room 1, T2=room 2 and T3=room 3), the temperature of the absorber room, the temperature of the outlet, ambient temperature, air velocity and solar radiation. The results showed that the average ambient temperature ranged from 30°C to 40°C. Meanwhile, the average temperature in the GHE vent dryer ranges from 69°C to 71°C. The drying air flow velocity in the environment reaches 1.3 m/s and on the ventilator 1.1 m/s. During the study, data on solar radiation was also obtained on average reaching 6.6 W.h/m 2 . The final conclusion of this study shows that the use of paraffin as a heat storage medium in the GHE vent dryer is able to maintain the temperature in the drying chamber for 4 to 5 hours when solar radiation is not present.